Application of Sharia Economic Principles of Qardh Agreements to E-Commerce: Study of Shopee Paylater Transactions - Mufidatul Himmah; Sania (Program Studi Ekonomi Syariah, Fakultas Agama Islam Universitas Islam Riau, 2023)
The presence of the Shopee application with the paylater feature is proof of world development in the field of technology that can provide convenience for consumers in shopping from anywhere and anytime. The provision of limits in technical payments can certainly also make it easier for consumers when shopping when they don't have money, by using the predetermined limit. This research aims to discuss the synchronization of the qard contract in Islamic transactions with the OJK protection system for Shopee pay later, which is often a topic of discussion for usury transactions. The method used in this research is descriptive qualitative, which describes the results of the research using explanations in words in detail or detail so that readers can understand the discussion that the researcher will raise through online research to find theories and use them wisely. This research is directed and focused on discussing library materials in the form of journals. The results of this research explain that shopee paylater is called qardh or loan contract. Shopee paylater which stipulates fines for late payments shows usury. This shows that there is continuous usury when users are late in paying bills that are due. Therefore, as smart consumers, we must be careful when using the Shopee PayLater feature to avoid delays in payments and usury.